(untitled) (Journal of human and social sciences, 2023)
Reconstruction is an urgent challenge that needs to be undertaken promptly, especially in heavily affected areas. Given the current state revenues and government spending, direct reconstruction by the state is very difficult. Therefore, mechanisms must be established to enable local and foreign investment to contribute effectively to the reconstruction process. Foreign investment is particularly crucial during the reconstruction and economic development phases. However, challenges exist, including the need to amend and update current legislation, as well as the need for clear strategies and visions to develop investment. This study discusses the role of investment law in reconstruction and addresses the challenges and obstacles facing investment and its contribution to reconstruction. Keywords: Investment Law, Reconstruction, Foreign Investment, Economic Development.